2013
DOI: 10.1177/0363546512470625
|View full text |Cite
|
Sign up to set email alerts
|

Fasciotomy and Surgical Tenotomy for Recalcitrant Lateral Elbow Tendinopathy

Abstract: Ultrasonic microresection of diseased tissue with the TX1 device provides a focally directed, safe, specific, minimally invasive, and well-tolerated treatment for recalcitrant lateral elbow tendinopathy in an office-based or ambulatory surgical setting with good evidence of some level of efficacy in 19 of 20 patients (95%) that is sustained for at least 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 27 publications
5
27
1
Order By: Relevance
“…In recent years, a novel technique termed as ultrasoundguided percutaneous tenotomy (UGPT) has been reported as a safe and effective procedure for the treatment of LE, with durable improvements in terms of symptoms, function, and ultrasound imaging at 1-year follow-up [98]. Barnes et al [99] reported similar outcomes for 19 patients with chronic, refractory lateral, or medial elbow tendinopathy up to 1 year after the procedure.…”
Section: Percutaneous Surgerymentioning
confidence: 99%
“…In recent years, a novel technique termed as ultrasoundguided percutaneous tenotomy (UGPT) has been reported as a safe and effective procedure for the treatment of LE, with durable improvements in terms of symptoms, function, and ultrasound imaging at 1-year follow-up [98]. Barnes et al [99] reported similar outcomes for 19 patients with chronic, refractory lateral, or medial elbow tendinopathy up to 1 year after the procedure.…”
Section: Percutaneous Surgerymentioning
confidence: 99%
“…Using ultrasonic energy, this minimally-invasive procedure is able to debride pathologic tissue through a needle-like device placed within the tendon. In a case series of 20 patients with recalcitrant lateral epicondylitis, percutaneous ultrasonic microtenotomy demonstrated improvement in pain and function in 95% of patients treated at one year 58 . A follow-up on the same patient population demonstrated sustained clinical efficacy at three years, with all patients demonstrating a reduction in tendon thickness and 95% exhibiting a resolution of tendon hypervascularity 59 .…”
Section: Operative Management Of Tendinopathymentioning
confidence: 98%
“…Platelet-rich plasma and other autologous blood preparations have shown promise and are currently one of the hottest topics in tendon care. Percutaneous fasciotomy and tenotomy using ultrasonic energy (FAST procedure) is an interesting technique that has recently shown significant improvements in VAS, DASH scores, and morphological characteristics of tendon quality [2]. For all of these procedures, an increase in the use of ultrasound imaging to guide injection placement has the potential to increase our effectiveness.…”
Section: How Do We Get There?mentioning
confidence: 99%